Preliminary study of motorcycle lanes capacity in Malaysia - Hamid, Hussain; Law, Teik Hua; Radin Sohadi, Radin Umar (2001)
In Malaysia, motorcycles represented more than halves of all registered vehicle population. In addition, motorcyclist contributed almost 70% of all injuries I accidents on Malaysian roads. This alarming figure warrants for some roads safety strategies targeted specifically on motorcyclists. An effective engineering approach to tackle this problem is by segregating these vulnerable roads users from other motorized traffic through the provision of an exclusive motorcycle lane. Prior to constructing an exclusive motorcycle lane, there is a need to understand the parameters involved in capacity analysis used to assess the supply side, quality of flow and also the design life of this facility. In order to comprehend the relative significance of these parameters, data were collected at five spots along the existing motorcycle track of Federal Highway Route 2. The Greenshields’ method and multiple regression technique were then applied to scrutinize the data. The analysis resulted with the development of preliminary models on the relationships between flow, density and mean speed on motorcycle lanes. Further, a simple regression model that relates the saturation flow (capacity) and effective width of motorcycle lane was established.